Леди-мафия: [роман] / Владимир Колычев - Колычев Владимир Григорьевич (Эксмо - Пресс, 2001)
Экземпляры: ФО-3 (201410) / Инвентарный номер: 50345 / Цена: 80.00 / Сис.шифр: Р2 / Авт.знак: К 61 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6